1996
DOI: 10.1088/0268-1242/11/11/001
|View full text |Cite
|
Sign up to set email alerts
|

Electron states in a two-dimensional ring - an exactly soluble model

Abstract: An exactly soluble model for a two-dimensional ring is proposed. Using this model, we have obtained analytically the energy spectrum and wavefunctions for a ring in the presence of a uniform magnetic field and a thin magnetic flux. The model can also describe quantum dots, anti-dots, one-dimensional rings and straight two-dimensional wires, which provides an integrated picture for the electron states and their magnetic field response in these geometries. The simplicity and the flexibility of the model make it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 53 publications
(69 reference statements)
5
161
1
4
Order By: Relevance
“…(1). In the single particle picture a ring of finite width can be solved analytically 22,23 . We have used the one-dimensional energy spectrum to keep the calculations tractable, which is a good approximation for thin rings.…”
Section: Modelmentioning
confidence: 99%
“…(1). In the single particle picture a ring of finite width can be solved analytically 22,23 . We have used the one-dimensional energy spectrum to keep the calculations tractable, which is a good approximation for thin rings.…”
Section: Modelmentioning
confidence: 99%
“…[33][34][35][36][37]. Further, by assuming that the parameter δ = E 0 ω is small, we have shown that the spectrum of energy is proportional to 2 in contrast to previous studies of the analogous confinement of a neutral particle with a permanent magnetic dipole moment to a quantum dot induced by noninertial effects [30,31], where the energy levels are proportional to in an analogous way to the Tan-Inkson model for a quantum dot [53][54][55]. Moreover, we have also obtained the Page-Werner et al term [11][12][13], which corresponds to the coupling between the quantum number and the angular velocity ω.…”
Section: Discussionmentioning
confidence: 54%
“…Comparing the result (12) with the studies of the confinement of particles to a quantum dot made in [33][34][35][36][37], we have in this case that the geometry of the spacetime plays the role of a hard-wall confining potential due to the presence of noninertial effects that restrict the physical region of the spacetime where the wave function can be defined. Moreover, we have that the energy levels (12) are proportional to 2 in contrast to recent studies of the analogous confinement of a neutral particle to a quantum dot [30,31] (given by imposing a condition on the induced fields µλ ω), where the energy levels are proportional to in an analogous way to the Tan-Inkson model for a quantum dot [53][54][55]. Hence, the spectrum of energy (12) is analogous to having a neutral particle with a permanent electric dipole moment confined to a quantum dot described by a hard-wall confining potential [33][34][35][36][37].…”
Section: Analogous Confinement Of a Neutral Particle To A Quantum Dotmentioning
confidence: 75%
See 1 more Smart Citation
“…In recent years, the study of the confinement of particles in two-dimensional quantum rings and quantum dots have been made in different models [32][33][34][36][37][38][39][40][41][42][43][44]. An interesting discussion about the behaviour of a quantum particle confined to a quantum two-dimensional quantum ring and a quantum dot was made in [32][33][34][40][41][42][43], where it has been shown that the spectrum of energy can be either non-parabolic [40][41][42] or parabolic [32][33][34]43] in relation to the principal quantum number…”
mentioning
confidence: 99%